Upregulation of Intestinal Barrier Function in Mice with DSS-Induced Colitis by a Defined Bacterial Consortium Is Associated with Expansion of IL-17A Producing Gamma Delta T Cells - Li, Ming; Wang, Bing; Sun, Xiaotong; Tang, Yan; Wei, Xiaoqing; Ge, Biying; Tang, Yawei; Deng, Ying; He, Chunyang; Yuan, Jieli; Li, Xia (Frontiers in Immunology, 2017)
Bacterial consortium transplantation (BCT) is a promising alternative to fecal microbiota transplantation (FMT) in treating inflammatory bowel disease (IBD). Here we showed that a defined bacterial consortium derived from healthy mice was able to enhance the intestinal barrier function of mice with dextran sulfate sodium (DSS-) induced colitis. Interestingly, we found that the bacterial consortium significantly promoted the expansion of IL-17A-producing γδT (γδT17) cells in colonic lamina propria (cLP), which was closely associated with changing of intestinal microbial composition. The increased IL-17A secretion upon treatment with microbial products derived from the bacterial consortium was accompanied with up-regulation of TLR2 expression by γδT cells, and it might be responsible for the up-regulation of mucosal barrier function through IL-17R-ACT1-mediated recovery of the disrupted occludin subcellular location. Changing of some specific microbial groups such as Bifidobacterium and Bacillus spp. was closely correlated with the promotion of TLR2+γδT cells. Our results support that BCT can restore the alliance between commensal microbiota and intestinal γδT cells, which contributes to the improvement of intestinal barrier function. This study will provide new insight into the development of bacteria transplantation therapy for the treatment of IBD.